Client satisfaction with pharmacy services and associated factors at Yekatit 12 Hospital Medical College, Addis Ababa, Ethiopia - Mekdes Tamiru Yizengaw; Bekele Simegn Demissie; Beimnet Taye Mekonnen; Birknesh Tamire Haile; Sosina Fikadu Mulugeta; Ekram Kemale Mohmmed; Samrawit Birhanu Alemu; Melaku Birhanu Alemu (PLoS ONE, 2026)
Background Client satisfaction is a crucial indicator of healthcare quality, influencing treatment adherence, continuity of care, and overall health outcomes. However, there is limited evidence on client satisfaction with pharmacy services in Ethiopia. This study aims to assess client satisfaction levels and their determinants in pharmacy services at Yekatit 12 Hospital, Addis Ababa. Methods A hospital-based cross-sectional study was conducted at Yekatit 12 Hospital Medical College, from 21 April 2025–15 May 2025. A total of 422 adult patients and caregivers were selected using systematic random sampling from five pharmacy units. Data were collected through a structured, interviewer-administered questionnaire. The questionnaire included sociodemographic characteristics and measures of satisfaction. Responses were measured on a five-point Likert scale, and the mean score was used to categorise participants as satisfied or dissatisfied. Data were analysed using STATA software, and multivariable logistic regression identified factors associated with satisfaction. Ethical approval was obtained from the Institutional Review Board (IRB) of Yekatit 12 Hospital Medical College (Reference number: RPO/934/25). Results Overall, 49.76% of participants were satisfied with outpatient pharmaceutical services. Participants with secondary education or higher had significantly lower odds of satisfaction compared with those with no formal education (AOR = 0.23; 95% CI: 0.07–0.79). Clients who did not receive all prescribed medications were also less likely to be satisfied (AOR = 0.35; 95% CI: 0.20–0.60). In contrast, ART pharmacy users had higher odds of satisfaction compared with outpatient pharmacy users (AOR = 3.27; 95% CI: 1.38–7.78). Conclusion Client satisfaction with pharmacy services at Yekatit 12 Hospital was low. Educational status, type of pharmacy service, and medication availability were associated with satisfaction levels. Higher satisfaction in the ART pharmacy underscores the value of specialised service. Strengthening drug supply systems, enhancing staff-client interaction, and improving service processes may increase satisfaction across pharmacy units.